A preliminary investigation of the relationship between dispositional mindfulness and eating disorder symptoms among men in residential substance use treatment. (2nd January 2017) - Elmquist, JoAnna; Shorey, Ryan C.; Anderson, Scott E.; Stuart, Gregory L.
Abstract: The comorbidity between eating disorders (EDs) and substance use disorders (SUDs) is of particular concern given the high rates of mortality, relapse and poor treatment outcomes associated with both disorders. As a result, there has been a growing impetus within the field to elucidate factors that might influence and aid treatment for this comorbidity. One such factor is dispositional mindfulness, as past literature has demonstrated a significant relationship between mindfulness and both EDs and SUDs. However, we are unaware of any research that has examined the relationship between dispositional mindfulness and ED symptoms in a sample of men in residential treatment for SUDs. Medical records from 152 men were included in the current study. Alcohol and drug use and problems, ED symptoms and dispositional mindfulness were assessed with self-report measures. Hierarchical regression analysis indicated that dispositional mindfulness was inversely related to ED symptoms after controlling for alcohol use, drug use and age. Although results are preliminary and continued research in this area is needed, our findings suggest that there may be potential usefulness in targeting and enhancing mindfulness among patients in residential treatment for SUDs with cooccurring psychiatric symptoms (e.g., EDs).